Visual literacy : an investigation into the interpretation of visuals among primary learners - Wei, Elysia Chua Chiat (Universiti Malaysia Sarawak, (UNIMAS), 2014)
This research investigated the interpretation of visuals among primary school learners based on currently prescribed textbooks. Ten primary three learners from two schools were used as samples for this study. This case study employs a thinkaloud task that requires participants to label 10 visuals and a semi-structured interview to determine the learners’ interpretations and how they derive their interpretations. These sessions are transcibed and analysed. From the findings, a model is developed to illustrate how primary learners interpret visuals. Results from the research showed a wide range of interpretations that are influenced by the knowledge of gender roles, understanding of visual conventions, common knowledge, prior experiences, identification of salient features, facial gestures and also expressions. This inevitably implies that primary school learners have varying levels of visual literacy and that they encounter difficulties in undertanding visuals due to their different backgrounds and experiences. It is found that, iconic images are easier for learners to interpret; therefore, the presence of additional contextual elements in visuals is critical to help learners in understanding visuals more accurately. Contextual elements can be in the form of texts, colours and relevant visual elements that can help define the image further. This study also highlights the need to explicitly teach these young learners how to critically interpret visuals; in particular symbol-based visuals, as some participants in this study relied only on context to interpret visuals.